Students’ perception of bilingualism use in a classroom at senior high school: a case study - Amira Muflicha Daraini; Nur Arifah Drajati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
English is a language that is normally used around the world. It is the legitimate language of 53 nations. Thus, many people want to learn English. Bilinguals are present in every country, social class, and the global economy. It is demonstrated by bilingual class or two languages (English and Indonesian) class, which is really popular in Indonesia. One of the levels which provides bilingual class is the level of senior high school. English is not only taught in English subject, but also in the other subjects. This research addressed the students' perception of the use of bilingualism in the teaching and learning process at senior high school. A qualitative approach as a basic framework was used in this research with a case study method. The participants of this research were 20 students of female and male. The data were taken with a questionnaire and interview. There were only three students involved in the interview session. The results show that most students gave positive perceptions of the use of English; understanding the explanation easily, feeling comfortable during the class, and enriching their vocabulary. This research can contribute to the policy-making of schools which intend to adopt a bilingual education program.